Pengenalan Penggunaan Software Perancangan Pesawat Di Industri Penerbangan Pada Siswa SMK Muhammadiyah I Temon Kulon Progo - Djarot Wahju Santoso (Institut Teknologi Dirgantara Adisutjipto, 2019)
The era of globalization with all its implications is one of the triggers of rapid changes that occur in various aspects of people's lives and if there is no serious effort to anticipate it, it will become a very serious problem. The field of education has a large responsibility, especially in the change of preparing strong human resources so that they are able to live in harmony with the changes themselves. This community service activity was held at Muhammadiyah I Vocational School Temon Kulon Progo with the aim of introducing the use of CATIA aircraft design software in the aviation industry. Implementing community service activities in the context of introducing aircraft design software in the aviation industry is carried out for 2 days in accordance with existing competencies in the relevant school curriculum. This activity is able to provide knowledge that can be used as a reference in improving student learning competencies.